The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/infdis/jiy704
|View full text |Cite
|
Sign up to set email alerts
|

Gardnerella vaginalis and Prevotella bivia Trigger Distinct and Overlapping Phenotypes in a Mouse Model of Bacterial Vaginosis

Abstract: Background Bacterial vaginosis (BV) is a common imbalance of the vaginal microbiota characterized by overgrowth of diverse Actinobacteria, Firmicutes, and Gram-negative anaerobes. Women with BV are at increased risk of secondary reproductive tract infections and adverse pregnancy outcomes. However, which specific bacteria cause clinical features of BV is unclear. Methods We previously demonstrated that Gardnerella vaginalis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 52 publications
4
88
1
4
Order By: Relevance
“…In this model, G. vaginalis titers in the vagina and uterine horns were not significantly different between mono and co-infected groups. Consistent with the G. vaginalis inoculation model reported in 2013, no clinical signs of inflammation were observed in the vaginas or uterine horns of mono or co-infected animals (Gilbert et al, 2013(Gilbert et al, , 2019.…”
Section: G Vaginalis Encourages Ascending Uterine Infection By Prevosupporting
confidence: 87%
See 3 more Smart Citations
“…In this model, G. vaginalis titers in the vagina and uterine horns were not significantly different between mono and co-infected groups. Consistent with the G. vaginalis inoculation model reported in 2013, no clinical signs of inflammation were observed in the vaginas or uterine horns of mono or co-infected animals (Gilbert et al, 2013(Gilbert et al, , 2019.…”
Section: G Vaginalis Encourages Ascending Uterine Infection By Prevosupporting
confidence: 87%
“…In addition to findings that certain strains of Gardnerella can reproduce features of BV in experimental models, there is also evidence to support the conclusion that Gardnerella can influence whether other organisms cause pathophysiology. Specifically, vaginal colonization by the JCP8151B strain caused mice to experience higher titer ascending uterine infections by Prevotella bivia compared to animals that received only P. bivia (Gilbert et al, 2019). The JCP8151B strain was also able to trigger recurrent UTI caused by uropathogenic E. coli that re-emerged from long lasting reservoirs inside epithelial cells in response to bladder exposure to Gardnerella, but not Lactobacillus crispatus (Gilbert et al, 2017).…”
Section: Can Gardnerella Reproduce Features Of Bv In Experimental Modmentioning
confidence: 97%
See 2 more Smart Citations
“…However, Lactobacillus -dominated vaginal microbiota is displaced by the overgrowth of Gardnerella species and other BVAB when vaginal dysbiosis happens [ 100 ]. Recent studies have demonstrated that the synergistic interactions between BVAB such as G. vaginalis and A. vaginae significantly enhanced the severity of BV by increasing bacterial burden [ 101 , 102 ]. Another important feature of BV is polymicrobial biofilm formation mainly by G. vaginalis , while the presence of other co-colonised BVAB was shown to enhance the biofilm thickness of G. vaginalis growth [ 85 , 103 105 ].…”
Section: Indigenous Vaginal Microbiota In Womenmentioning
confidence: 99%